THU0605 Omega-3 Fatty Acids Associates with Decreased Pain, Independent of Inflammation, in MTX Treated Early RA Patients. (15th July 2016) - Lourdudoss, C.; Wolk, A.; Di Giuseppe, D.; Westerlind, H.; Klareskog, L.; Alfredsson, L.; van Vollenhoven, R.; Lampa, J.
Abstract : Background: Dietary intake of omega-3 fatty acids (FA) may play a role in etiology of RA [1] and has also been shown to be anti-inflammatory in RA [2]. Increased intake of omega-6 FA as well as omega-6:3 FA ratio are associated with inflammation in RA [3]. However, little is known about how omega-3 FA may affect pain in RA. Objectives: To study the association between omega-3, omega-6, omega-6:3 FA ratio and pain, despite inflammatory control, after three months of MTX treatment in early RA patients. Methods: We included newly diagnosed RA patients with MTX monotherapy from Epidemiological Investigation of Rheumatoid Arthritis (EIRA) study linked to clinical data from Swedish Rheumatology Quality register (SRQ). Data on omega-3, omega-6, and omega-6:3 FA ratio (dietary questionnaires) were linked with data on self-assessed pain after three months of MTX treatment. Pain despite inflammatory control (Remaining Pain) was defined based on the Patient Acceptance Symptom Scale (PASS)[4] together with low systemic inflammation (VAS pain >40mm and CRP<10mg/L). Statistical analysis: logistic regression adjusted for age, sex, smoking, education, BMI, energy intake and omega-3 FA supplementation. Results: We included 591 patients (median age: 55 years; females: 70.6%; ACPA+: 67.9%). Mean values for clinical measures at baseline were: DAS28 5.2±1.3, VAS pain 53.9±24.7 and HAQ 1.1±0.6. Mean BMI was 25.8±4.7 kg/m 2 . Omega-3 FA supplements were used by 19.5% of the patients. After three months, 92 patients (15.6%) had Remaining Pain. These patients had lower intake of omega-3 FA compared to those without Remaining Pain (0.6±0.4 vs. 0.7±0.3 g/day, p=0.004). Omega-3 FA intake was inversely associated with Remaining Pain (OR=0.5 [95% CI 0.3–0.9]), after adjustment. Omega-6:3 FA ratio but not omega-6 FA alone was directly associated with remaining pain (OR=2.3 [95% CI 1.3–4.2]). Similar ORs were found after adjustment for ACPA and physical activity. Omega-3 FA was not associated with CRP or EULAR response at the follow-up. Conclusions: Omega-3 FA was inversely associated with Remaining Pain and omega-6:3 FA ratio was directly associated with Remaining Pain. These associations were independent of inflammation. Our data suggest that dietary omega-3 FA may dampen the development of chronic pain in early RA. References: Di Giuseppe, D., et al., Long-term intake of dietary long-chain n-3 polyunsaturated fatty acids and risk of rheumatoid arthritis: a prospective cohort study of women. Ann Rheum Dis, 2014. 73(11): p. 1949–53. Ariza-Ariza, R., M. Mestanza-Peralta, and M.H. Cardiel, Omega-3 fatty acids in rheumatoid arthritis: an overview. Semin Arthritis Rheum, 1998. 27(6): p. 366–70. Sundrarjun, T., et al., Effects of n-3 fatty acids on serum interleukin-6, tumour necrosis factor-alpha and soluble tumour necrosis factor receptor p55 in active rheumatoid arthritis. Journal of International Medical Research, 2004. 32(5): p. 443–454. Pham, T. and F. Tubach, Patient acceptable symptomatic state (PASS). Joint Bone Spine, 2009. 76(4): p. 321–3. Disclosure of Interest: None declared